Relationship Between Foveal Threshold and Macular Structure/Function/Vessel Density in Glaucoma. Issue 2 (February 2020) - Jeong, Daun; Won, Hun Jae; Jo, Youn Hye; Song, Min Kyung; Shin, Joong Won; Kook, Michael S.
Abstract : Purpose: To investigate the hypothesis that macular structure, function, and vessel density (VD) measurements can predict foveal threshold (FT) outcomes in glaucomatous eyes. Materials and Methods: One hundred ninety-five eyes from 195 subjects (134 subjects with early-to-moderate stage open-angle glaucoma and 61 healthy controls) who underwent optical coherence tomography angiography imaging and 24-2 visual field (VF) testing with FT measurements on the same day were retrospectively enrolled in this study. The association of FT with macular structural/functional/VD measurements was evaluated using partial correlation analyses with adjustment for age and linear regression analyses. Results: FT showed significant correlations between the thickness of the macular ganglion cell-inner plexiform layer (mGCIPL) ( r =0.330, P <0.001) and the mean sensitivity (MS) of the central 5 and 10 degrees VF points ( r =0.448, P <0.001 and r =0.361, P <0.001). Significant correlations were also found between FT and VD measurements at the inferior and superior parafoveal sectors ( r =0.455, P <0.001 and r =0.438, P <0.001). In multivariate linear regression analyses controlling the covariates, the thickness of the mGCIPL, central 5 degrees VF MS, and parafoveal VD were significantly associated with FT (all P <0.001). There was also a significant association between FT and logMAR best-corrected visual acuity (β=−5.647, P <0.001). Conclusions: Macular VD along with mGCIPL thickness and central 5 degrees VF MS independently predict FT outcomes even in the eyes of patients with early-to-moderate stage open-angle glaucoma.